Reducing the scale? From global images to border crossings in medical tourism. (27th June 2016) - CONNELL, JOHN
Abstract: International medical travel has increased in the last 20 years, becoming more diverse and complex, although definitions and data on its growth and structure are inadequate. Many countries, especially in the Global South, have sought to develop medical tourism for both strategic and defensive reasons. Few have been successful. Standard descriptions and images of medical tourism suggest global markets, elite patient travellers and the dominance of cosmetic surgery, alongside the privatization and corporatization of hospital chains. Most international medical travel is, however, short‐distance, diasporic, across adjacent and nearby borders, and of relatively poor patients seeking cheaper, more effective or available care in appropriate cultural contexts, for straightforward procedures. Social networks, rather than the internet, shape choices and decisions on destinations. Porous international borders are crucial to medical travel and have resulted in the emergence of formal trans‐border health regions in the North and spontaneous informal regions in the South, alongside some regional hubs and hierarchies. Globalization is less significant than the grassroots transnationalism of borderland health care.